Community apple pollination rewards tribal people - Chandel, R S; Kumar, Rakesh; Dhiman, Sushil; Kumar, Pramod; Sharma, Rajinder (Indian Horticulture, 2019)
The low pollinizer to main cultivar ratio and declining Indian honeybees as pollinator has been identified as the major constraint of apple productivity in tribal Kinnaur district of Himachal Pradesh. A scientific intervention on managed pollination at community level was planned in an area of 110 ha apple orchards belonging to 184 households in Gram Panchayat Telangi. This success story presents an exceptional outcome where tribal farmers’ worked at community level, shared 50% of intervention cost and monitored the intervention through its committee, VCRMC. The community intervention resulted in an average enhancement of 19.4% fruit yield and monetary income of `17,496/ family, besides, an expectation of 1.0 tonne honey yield annually.